Seaweed Waste in Nusa Dua: An Analysis of Environmental Challenges and Recycling Opportunities - Moh Rizal Ngambah Sagara; I Wayan Koko Suryawan (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2023)
Nusa Dua, a prominent tourist destination, grapples with the multifaceted challenge of seaweed waste accumulation. Through a qualitative approach anchored in extensive literature review and observational data, this study delves into the environmental implications and the latent opportunities that seaweed waste presents. The research reveals significant potential repercussions ranging from ecological disturbances to potential economic downturns linked to reduced tourist appeal. However, it also uncovers various recycling possibilities, including biofuel production and sustainable packaging, offering viable solutions to the problem. This paper underscores the necessity of collaborative action, innovative policies, and community engagement to transform Nusa Dua's seaweed waste challenge from an environmental concern into an opportunity for sustainable development.